Origin, geochemical characteristics and filling pathways in the Shadegan oil field, Dezful Embayment, SW Iran. (February 2021) - Asemani, Morteza; Rabbani, Ahmad Reza; Sarafdokht, Hashem
Abstract: The Shadegan oil field is one of the fields in the central part of the Dezful Embayment. Little or no geochemical studies have been performed previously in this field. This paper provides valuable information to answer most of the geochemistry ambiguities and issues in this field. Different techniques were used to investigate the genetic types of Asmari and Bangestan reservoirs. Structural characteristics of asphaltenes, biomarker fingerprints, and V/Ni ratio indicates that all oils in the Shadegan field have similar source rock(s) and belong to one oil family. The homologous series of normal alkanes distribution and the absence of 17α(H) 25-hopane reveals that biodegradation has not affected oil samples and planktons/algal or higher plants are dominating organic matters, proved by hopanes/steranes ratio. The Pr/Ph < 1, 0.49 < V/(V + Ni) < 0.81, and homohopanes distribution implied an anoxic condition during source rock deposition. The DBT/Ph, C24/C23 tricyclic terpanes, C22/C21 tricyclic terpanes, C29/C30 hopane, diasterane/sterane ratios suggest that the contribution of clay to source rock was insignificant and source rock has composed of a mix shale and carbonate. Steranes show C29 > C27 > C28 pattern, and the ternary diagram of steranes confirmed that the source rock deposited in the open marine environment and oil samples originated from marine organic matters. All samples have been sourced from a source rock(s) older than the Upper Cretaceous, as shown by the oleanane ratio. The Kazhdumi Formation is the primary source rock in this field, and some contributions from other source rocks might have occurred. In general, samples indicate maturity before the peak of the oil window in which the Bangestan samples have lower maturity regarding the Asmari samples based on aromatic and saturate maturity parameters. The tracing of oil filling pathways by isopleth maps of 4-/1-MDBT and C29 sterane 20S/(20S + 20R) ratios revealed that each reservoir had been charged from several directions. Although the Upper Asmari and Bangestan reservoirs have been charged laterally, the Lower Asmari has been charged vertically and laterally. Highlights: Structural similarity of asphaltenes, biomarkers, and trace elements was used for the investigation of genetic types. The Kazhdumi source rock is the primary source rock in the generation of crude oils in the Shadegan field. Crude oils have been sourced from a shale-carbonate lithology source rock with marine organic matters. The tracing of oil filling pathways showed each reservoir had been charged from several directions.